2015
DOI: 10.1118/1.4914419
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating multislice imaging into x‐ray CT polymer gel dosimetry

Abstract: Multislice CT imaging has been evaluated for CT PGD and found to be the superior technique compared to single slice imaging in terms of the time required to complete a scan and the tube load characteristics associated with each scanning method. The implementation of multislice scanning is straightforward and expected to facilitate routine gel dosimetry measurements for complex dose distributions in modern RT centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The factors that affect noise are the size of the subject, scattered rays, tube voltage, tube current, the size of pixel, and reconfiguration method [13]. Although some studies about how these various factors affect Noise are being reported [14], there was no report on how radioisotope affects Noise. Therefore, the study investigated how radioisotope impact on CT number and Noise.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that affect noise are the size of the subject, scattered rays, tube voltage, tube current, the size of pixel, and reconfiguration method [13]. Although some studies about how these various factors affect Noise are being reported [14], there was no report on how radioisotope affects Noise. Therefore, the study investigated how radioisotope impact on CT number and Noise.…”
Section: Discussionmentioning
confidence: 99%
“…All gels were imaged on an Optima CT580 multislice CT scanner (GE Medical Systems, Milwaukee, WI, USA) using the settings and procedures described in previous work (Maynard et al 2017(Maynard et al , 2018 with parameters that have been optimized for x-ray CT gel dosimetry (Hilts et al 2005, Johnston et al 2015. Briefly the scanning parameters used were: tube voltage=120kV, tube current=200 mA, gantry rotation time=1 s, slice thickness=2.5 mm, FOV=25×25 cm 2 , reconstruction algorithm= STANDARD, and images acquired per slice=25.…”
Section: X-ray Ct Imagingmentioning
confidence: 99%
“…X-ray CT is an appealing imaging modality for dosimeter read out as it is well developed, relatively easy to implement and readily available within the radiation therapy environment. In x-ray CT polymer gel dosimetry, the polymerization reactions in an irradiated dosimeter lead to changes in linear attenuation coefficient within the gel which can then be measured using x-ray CT. As the signal in this type of measurement is quite low, initial work in this field consisted of increasing dose sensitivity of the gel (Jirasek et al 2010, Chain et al 2011), optimizing CT scanning protocols for low contrast resolution (Hilts et al 2005, Kakakhel et al 2011, Johnston et al 2015 and developing image processing and calibration techniques (Hilts and Jirasek 2008, Jirasek and Hilts 2014. As x-ray CT polymer gel dosimetry has evolved, investigations into clinical applications have started to emerge (Johnston et al 2012, Chiu et al 2014, Maynard et al 2017 including a preliminary study into the use of onboard cone beam CT for gel read out (Adamson et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A method using a compensation filter (where the aluminium layer of either side of the target is increased in thickness on one side) was developed by Mori et al, 2005, to eliminate potential radiation damage to patients. Heel effect corrections based on simple first-order beam hardening (Braun et al, 2010), and a slice-by-slice background subtraction approach (Johnston et al, 2015) have also been proposed. However, these approaches have limitations in that their application requires detailed understanding of the target composition and geometry, hence additional specialist input.…”
Section: The Heel Effect In Medical Applicationsmentioning
confidence: 99%